Thermal Properties of Hybrid Nanofluid with Different Concentration - Mohd. Uwais Roslan; Nor Azwadi Che Sidik; M’hamed Beriache (Journal of Advanced Research Design, 2024)
Hybrid nanofluid is important as it has many applications in thermal related technology. The performance of a nanofluid is determined by its thermal properties. The thermal properties of the hybrid nanofluid are affected by many factors such as mixing ratio and temperature. The purpose of the study is to study the effect of different ratio concentration of hybrid nanofluid and temperature on the thermal properties. The thermal properties to be studied were thermal conductivity, viscosity, specific heat capacity and density. For this study, the mixing ratio concentration of Al2O3/TiO2 hybrid nanofluid samples was varied in order to see the difference between the thermal properties of each sample. The effect of temperature toward the samples was also tested. Results showed that samples with the highest ratio concentration of Al2O3 have the highest thermal conductivity and density while also having the lowest measurement of viscosity. However, samples with the highest value of specific heat capacity were unable to be determined due to the minimal difference between the results of the sample. The other results show that the increase in temperature causes the thermal conductivity and specific heat capacity to increase while the viscosity and density decrease. From the findings, this research can help future studies regarding the preparation and thermal properties of the Al2O3/TiO2. This research also can be a proof that this nanofluid be an alternative in any thermal related application.